INDIVIDUAL COUNSELING SERVICE TO REDUCE AGRESSIVE BEHAVIOR STUDENT AT SMK NEGERI 1 MANADO - Austin Palohon; Ariantje Sundah; Deklay Nainggolan (Prodi Bimbingan Konseling Universitas Negeri Manado, 2023)
Individual counseling, namely guidance and counseling services that allow students or counseling to get face-to-face direct services (individually) with the lead teacher in the context of discussing the staging of personal problems suffered by counseling. This approach sees counseling as a rational process that emphasizes present and present behavior. Self-Responsibility or self-responsibility becomes human awareness of intentional or unintentional behavior or actions. Responsibility can be a manifestation of awareness and obligation for humans. This study aims to increase student self-responsibility in aggressive behavior, so that students (counselees) can manage time and can study for social academics. The impact of implementing individual counseling in teaching and learning activities for 10th grade students of SMK Negeri 1 Manado. This research was carried out in less than 2 months for the 2022 school year. Namely, on three students who demonstrated weak self-responsibility. The research procedures used in this study were (1) planning, (2) action implementation, (3) observation and monitoring, (4) analysis and reflection. The criterion for success in this study is a change in self-responsibility manifested in behavior that prioritizes learning from weak to strong to create a successful identity. After individual counseling actions the counselors can show changes that indicate an increase in self-responsibility in dealing with the learning process in the classroom. preparing to take exams, entering assignments on time can help friends to study hard as a self-commitment to change aggressive behavior. show progress in their respective learning outcomes.